ANALISIS EKSERGI MODUL PV BERDASARKAN SPEKTRUM PANJANG GELOMBANG CAHAYA MATAHARI - Dadan Hamdani; Lambang Subagio (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
PV modul performance can be evaluated in terms both energy and exergy based on wavelengths spectrum of the sun method, which take into account the contribution of chemical potential in term photonic energy and exergy corresponding to photonic energy of a PV module during tested (09:00 – 15:00). Based on this method, it is found that effect of wavelength of visible spectrum (300 – 800 nm) is essential on the PV performance and as the result of this evaluation is photonic energy higher than photonic exergy due to the irreversibilities of the real process. Keywords : energy and exergy, wavelengths spectrum, PV module , photonic, irreversibilities.